Pendidikan Budaya dan Karakter Bangsa Di Pesantren - Muhtarom, Mumuh (Balai Diklat Keagamaan Surabaya, 2020)
The weak of education in building the character and culture of the nation in Indonesia is marked by the many irregularities that occur among adolescents. The purpose of this study is to describe how to develop the culture and character of the nation in pesantren as a form of non-formal education development. The research method uses descriptive analysis by collecting and analyzing data from scientific studies relating to theories related to books, as well as research results published in journals. The Results of this research is developing cultural education and national character can be done by learning four ways, these were 1) interior regularity; 2) Coherence; 3) Firmness; and 4) loyalty. Meanwhile, to develop cultural education and national character in pesantren can be done if pesantren remains consistent in: 1) forming rabbani people; namely the perfect knowledge and piety to Allah SWT; 2) fostering superior humans who bashthatan fil ‘ilmi wal jismi; and 3) Islamic boarding schools prepare a generation that is tafaquh fiddin.